Dynamic Elastic Moduli of Teak Wood (Tectona grandis): Case study of Existing Buildings in Yogyakarta - Yosafat Aji Pranata; Olga Catherina Pattipawaej; Amos Setiadi (Universitas Islam 45, 2025)
This study aims to conduct experimental testing to obtain empirical values of the dynamic elastic moduli (MoEd) of wood, and to study its correlation with the static elastic moduli (MoE). The research method used is a quantitative method to obtain the parameters of progagation time and velocity data, by using a non-destructive test method on the structural components of columns and beams in existing buildings. The scope of the study is the dynamic elastic moduli data obtained from the results of previous studies, namely non-destructive testing on two existing wooden house buildings located in Sleman Regency, Special Region of Yogyakarta Province, Indonesia. The wood used is Teak wood species (Tectona grandis). The results of the study indicate that the MoEd of Teak wood (Tectona grandis) is obtained at 32891.34 MPa and MoE is 20007.17 MPa, with a ratio of MoE/MoEd of 0.608. The results of the study indicate that the wood in existing buildings is included in the category of strength class 1 with a quality code of E20 referring to SNI 7973.